2011
DOI: 10.1002/nau.21005
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the urinary sensation scale (USS)

Abstract: The USS is a valid and highly responsive measure of urinary urgency in men with OAB-LUTS and women with OAB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…Other studies [12,13] have reported that normal and abnormal urgency symptoms cannot be effectively discriminated. Therefore, many researchers calculate the sum, mode, or mean USS scores from the questionnaires [3]. Therefore, we used the USS questionnaire to compare urinary urgency with our new parameter, T2V.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies [12,13] have reported that normal and abnormal urgency symptoms cannot be effectively discriminated. Therefore, many researchers calculate the sum, mode, or mean USS scores from the questionnaires [3]. Therefore, we used the USS questionnaire to compare urinary urgency with our new parameter, T2V.…”
Section: Discussionmentioning
confidence: 99%
“…After each void, we measured the postvoid residual volume with a transabdominal ultrasonographic probe (BladderScan BVI 3000, Verathon Inc., Bothell, WA, USA). The patients completed urgency sensation scale (USS) questionnaires regarding their urgency symptoms during a single voiding at an uroflow room [3]. Symptom of urinary hesitancy was evaluated by asking the following question from each participant: "When you were ready to urinate, did you pass the urine immediately or did you wait?"…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients rated the urgency sensations associated with each micturition episode in their bladder diaries using the five-point Urinary Sensation Scale (from 1 ¼ no urgency to 5 ¼ UUI) 11 . An urgency episode was defined as a score of !3 on the Urinary Sensation Scale.…”
Section: Outcome Measurementmentioning
confidence: 99%
“…22 Urgency sensation scales or urgency severity scales (USS) have been developed to assess the urinary urgency in men with LUTS-associated OAB. 23 A high urgency severity score (USS) recorded in conjunction with a voiding diary and OAB wet were strongly associated with urodynamic DO. 24 BPH patients with DO may neglect the symptom of urgency due to abnormal bladder sensation, or negate the symptom by subconscious sphincter contraction to abort the overactivity.…”
Section: Male Luts and Oab E Backgroundmentioning
confidence: 99%